2016
DOI: 10.1097/md.0000000000003635
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Acupuncture and Pharmacopuncture in 80,523 Musculoskeletal Disorder Patients

Abstract: We investigated the range and frequency of significant adverse events (AEs) in use of pharmacopuncture and acupuncture using large-scale, single-center safety data as evidence supporting safety of acupuncture with pharmacopuncture, used extensively in Asia, is scarce. Status reports (nurse records in ambulatory and inpatient care units, and administrative event records) as a part of an internal audit at a Korean Medicine hospital specializing in the treatment of musculoskeletal disorders, patient complaints fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 23 publications
2
24
3
Order By: Relevance
“…Recent studies about AEs of acupuncture performed by regulated and qualified acupuncturists revealed the low incidence of serious AEs that could be fully recovered with adequate treatment. 6 14 15 By contrast to the results of these studies, 9 (18.8%) of 48 patients in our study presented with serious AEs including development of septic shock, admission to ICU admission and suffering permanent sequelae, and consequently they required long-term hospitalization, including ICU care. This difference may reflect the real-world situation.…”
Section: Discussioncontrasting
confidence: 97%
“…Recent studies about AEs of acupuncture performed by regulated and qualified acupuncturists revealed the low incidence of serious AEs that could be fully recovered with adequate treatment. 6 14 15 By contrast to the results of these studies, 9 (18.8%) of 48 patients in our study presented with serious AEs including development of septic shock, admission to ICU admission and suffering permanent sequelae, and consequently they required long-term hospitalization, including ICU care. This difference may reflect the real-world situation.…”
Section: Discussioncontrasting
confidence: 97%
“…It is composed of different peptides, proteins, and bioactive components, including melittin, phospholipase A2 (PLA2), and apamin [ 3 ]. These components have various pharmaceutical properties, including anti-inflammatory, antinociceptive [ 4 , 5 ], antiapoptosis, antiarthritic [ 6 ], and anticancer effects [ 1 , 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…BV therapy has been used for a long time [ 1 ] in various forms including the administration of live bee stings, the injection of BV, and BV acupuncture (BVA) [ 8 ]. Despite its clinical complications, toxicity or anaphylaxis, it is a safe form of acupuncture [ 6 , 9 , 10 , 11 ] and it has interesting pharmacological properties from a biotechnological point of view. Due to the bioactive compounds isolated from BV and its pharmacological actions, BVA is an effective treatment that is commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…In one survey of patients who had visited oriental medicine hospitals, 48% of responders preferred pharmacopuncture to other oriental medicine treatments, because it caused a rapid decrease in pain [1, 2]. Moreover, the safety investigation suggested that acupuncture/pharmacopuncture led to a lower range, frequency, and severity of significant adverse events [3]. …”
Section: Introductionmentioning
confidence: 99%